Binuclear gadolinium(III) complex based on DTPA and 1, 3-bis(4-aminophenyl)adamantane as a high-relaxivity MRI contrast agent. (1st May 2018) - Wan, Fuxian; Wang, Lipeng; Xu, Wenxin; Li, Changcheng; Li, Ying; Zhang, Chunbao; Jiang, Lin
Graphical abstract: A gadolinium(III) complex, bis(4-Gd-DTPA-aminophenyl)adamantane, the longitudinal relaxivity of it is 8.43 mM −1 Gd −1 s −1, which is higher than that of [Gd(DTPA)(H2 O)] 2− (3.86 mM −1 s −1 ) at 0.43 T (32 °C, pH 7.0). The T 1 -weighted imaging showed that it can enhance the contrast of images distinctly. Moreover, cytotoxicity tests indicated that the it exhibited less toxicity to L-02 cells. Abstract: A novel dimeric gadolinium(III) complex, bis(4-Gd-DTPA-aminophenyl)adamantane (5 ), was successfully synthesized using bis(4-aminophenyl)adamantane to link two Gd-DTPA units. All the intermediates and bis(4-Gd-DTPA-aminophenyl)adamantane (5 ) have been characterized by 1 H NMR, 13 C NMR, ES-API-MS, HR-ESI-MS, FT-IR and elemental analysis (EA). The longitudinal relaxivity of bis(4-Gd-DTPA-aminophenyl)adamantane is 8.43 mM −1 Gd −1 s −1 at 0.43 T (32 °C, pH 7.0), and 4.89 mM −1 Gd −1 s −1 at 3.0 T (32 °C, pH 7.4). The T 1 -weighted imaging in vitro showed that bis(4-Gd-DTPA-acetylaminophenyl)adamantane can enhance the contrast of images distinctly. But most of all, the kinetic inertness of bis(4-Gd-DTPA-aminophenyl)adamantane (5 ) was comparable to that of [Gd(DTPA)(H2 O)] 2− (Magnetvist®). Moreover, cytotoxicity tests indicated that the bis(4-Gd-DTPA-acetylaminophenyl)adamantane exhibited low toxicity to healthy liver cells (L-02 cells). These results demonstrate that the Gd(III) complex 5 may be a promising MRI contrast agent candidate.